2012
DOI: 10.1029/2012jd017684
|View full text |Cite
|
Sign up to set email alerts
|

Assimilating Doppler radar radial velocity and reflectivity observations in the weather research and forecasting model by a proper orthogonal‐decomposition‐based ensemble, three‐dimensional variational assimilation method

Abstract: [1] Doppler radar observations with high spatial and temporal resolution can effectively improve the description of small-scale structures in the initial condition and enhance the mesoscale and microscale model skills of numerical weather prediction (NWP). In this paper, Doppler radar radial velocity and reflectivity are simultaneously assimilated into a weather research and forecasting (WRF) model by a proper orthogonal-decompositionbased ensemble, three-dimensional variational assimilation method (referred t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 56 publications
1
22
0
Order By: Relevance
“…The assimilation of radar velocity cannot directly influence the physical process of rainfall, although it can affect the water vapor transport via the atmospheric motions. However, if the assimilated radar velocity cannot improve the atmospheric circulation predictions, the water vapor field may not be improved, and thus the rainfall forecasts may also be 15 found unimproved (Pan et al, 2012;Dong and Xue, 2013). In reality, the accuracy of the radial velocity data depends on the atmospheric refractive index, which is affected by the air density and the water vapor content (Montmerle and Faccani, 2010;Maiello et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The assimilation of radar velocity cannot directly influence the physical process of rainfall, although it can affect the water vapor transport via the atmospheric motions. However, if the assimilated radar velocity cannot improve the atmospheric circulation predictions, the water vapor field may not be improved, and thus the rainfall forecasts may also be 15 found unimproved (Pan et al, 2012;Dong and Xue, 2013). In reality, the accuracy of the radial velocity data depends on the atmospheric refractive index, which is affected by the air density and the water vapor content (Montmerle and Faccani, 2010;Maiello et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…This means that assimilating reflectivity impacts the thermodynamic and dynamic fields, 15 whereas radial velocity assimilation only influences the dynamic fields (Xiao and Sun, 2007;Abhilash et al, 2012). Li et al (2012) indicated that assimilating radial velocity every 30 min could improve the accuracy of rainfall (caused by hurricane) intensity prediction. Sun et al (2012) found that the pattern and location of forecasted rainfall were noticeably improved with radar reflectivity assimilation.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Single observation tests must be performed before the real data experiments. In the current single observation test, num_pseudo was set to 1 for each control variable at the grid point (9,30,30), which is the location relative to the total (40,60,60). The first dimension is the vertical model layer (9/40), the second dimension is latitude (30/60), and the last dimension is longitude (30/60).…”
Section: Single Observation Testmentioning
confidence: 99%